Arterioureteral Fistula: Treatment of a Hemorrhagic Shock with Massive Hematuria by Placing a Balloon Catheter - Nicolas Merzeau; Hervé Riquet; Ioannis Nicolacopoulos; Abbas Alame; Stéphane Larré (Case Reports in Urology)
Arterioureteral fistulas (AUF) are serious diseases with increasing incidence. This case report relates the management of AUF in a patient with a history of abdominal oncological surgery, pelvic radiotherapy, and a double J stent in place. The fistula was discovered during a hemorrhagic shock with massive hematuria. The bleeding was controlled by a balloon catheter which led to endovascular treatment consisting of a covered stent.